THE EUROPEAN EXPERIENCE OF INSTITUTIONALIZING OF THE POLITICAL OPPOSITION - Манойло, Д.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
Forms of institutionalizing of the political opposition, which exist today in the EU, are reviewed and analyzed in detail in the article. Consequences of a particular model of institutionalizing are studied. During the study, European states with different types of political systems and forms of government were considered. Both formal and informal mechanisms of functionalizing of the political opposition were studied on concrete examples.